Blockchain Implementation in E-Commerce to Improve The Security Online Transactions - Rangga Gelar Guntara; Muhammad Naufal Nurfirmansyah; Ferdiansyah (Kirana Publisher (KNPub), 2023)
The implementation of blockchain technology in E-commerce has become an increasingly important topic in recent years. Blockchain can bring big changes in the E-commerce industry, especially in increasing customer security and trust in online transactions. In this article, it is explained how blockchain technology can be used in E-commerce, such as in increasing the security of online transactions, product tracking, use of smart contracts, and digital identities. Nonetheless, the implementation of blockchain technology also has challenges and obstacles that need to be overcome, such as the considerable cost and time involved in system development and integration, as well as regulatory and legal issues related to the use of cryptocurrencies and digital identities. Therefore, the implementation of blockchain technology in E-commerce requires careful strategy and planning to maximize the benefits that this technology can provide.